A comparative appraisal of serum progesterone level during oestrous cycle in normal and repeat breeder crossbred cows with ovulatory problem - DEKA, K C; BORGOHAIN, B N; NATH, K C; GOSWAMI, J; BISWAS, R K; DAS, P K (The Indian Journal of Animal Reproduction, 2007)
An investigation to findout variation in the levels of serum progesterone during the estrous cycle was conducted on 117 crossbred cows; clinically the animal were catogorised as 10 normal breeders, 26 repeat breeders with anovulation, 30 repeat breeders with delayed ovulation and 51 repeat breeders with normal ovulation. On day 0, IO and 18 of the oestrous cycle the respective mean serum progesterone concentration were recorded as 0.58 ± 0.12, 6.50 ± 0.69 and 1.08 ± 0.05 ng/ml, in normal breeder cows; 0.26 ± 0.04, 0.45±0.05 and 0.25±0.04 ng/ml, in repeat breeder cows with anovulation; 0.57±0.28, 4.48±0.23 and 0.99±0.05 ng/ml in repeat breeder cows with delayed ovulation and 0.59±0.04, 4.76±0.14 and 1.19±0.01 ng/ml in repeat breeder cows with normal ovuiation. There was significant (P<0.0 1) variation in serum progesterone level between the days of oestrous cycle in repeat breeder cows with delayed ovulation and normal ovulation. Serum progesterone level in normal breeders on day 10 of oestrous cycle, was higher (P<0.0 I) than that on days 0 and 18, which was also found to be higher on day 10 in repeat breeders with anovulation, delayed ovulation and normal ovulation, revealing progesterone deficiency in repeat breeder cows.